Expression and characterization of an N-truncated form of the NifA protein of Azospirillum brasilense - C.Y. Nishikawa (Brazilian Journal of Medical and Biological Research, 2012)
Azospirillum brasilense is a nitrogen-fixing bacterium associated with important agricultural crops such as rice, wheat and maize. The expression of genes responsible for nitrogen fixation (nif genes) in this bacterium is dependent on the transcriptional activator NifA. This protein contains three structural domains: the N-terminal domain is responsible for the negative control by fixed nitrogen; the central domain interacts with the RNA polymerase σ54 co-factor and the C-terminal domain is involved in DNA binding. The central and C-terminal domains are linked by the interdomain linker (IDL). A conserved four-cysteine motif encompassing the end of the central domain and the IDL is probably involved in the oxygen-sensitivity of NifA. In the present study, we have expressed, purified and characterized an N-truncated form of A. brasilense NifA. The protein expression was carried out in Escherichia coli and the N-truncated NifA protein was purified by chromatography using an affinity metal-chelating resin followed by a heparin-bound resin. Protein homogeneity was determined by densitometric analysis. The N-truncated protein activated in vivo nifH::lacZ transcription regardless of fixed nitrogen concentration (absence or presence of 20 mM NH4Cl) but only under low oxygen levels. On the other hand, the aerobically purified N-truncated NifA protein bound to the nifB promoter, as demonstrated by an electrophoretic mobility shift assay, implying that DNA-binding activity is not strictly controlled by oxygen levels. Our data show that, while the N-truncated NifA is inactive in vivo under aerobic conditions, it still retains DNA-binding activity, suggesting that the oxidized form of NifA bound to DNA is not competent to activate transcription.